In‐Depth Analysis of the Necessity and Optimization Strategies for Adjuvant Radiotherapy Following Neoadjuvant Immunotherapy in the New Era of Esophageal Cancer Treatment - Guohui Liu; Yao Su; Yunlong He; Hanqing Hu (Cancer Innovation)
ABSTRACT As immunotherapy rises to prominence in cancer treatment, the therapeutic approach to esophageal cancer is undergoing significant transformations. This review emphasizes the necessity and optimization pathways for adjuvant postoperative radiotherapy after neoadjuvant therapy in patients with esophageal cancer in the immunotherapy era. Initially, we review the advancements in neoadjuvant treatment strategies. Subsequently, we evaluate the role of postoperative radiotherapy and the latest advancements in radiotherapy target volume definition and dose optimization following neoadjuvant therapy, as well as the implications of tumor immunotherapy on postoperative radiotherapy strategies. In conclusion, in the new era of immunotherapy, postoperative radiotherapy following neoadjuvant therapy for esophageal cancer holds significant value. Optimization strategies should follow individualized treatment principles and comprehensively consider tumor biology, patient status, and treatment resources to achieve optimal therapeutic outcomes and quality of life, thereby driving continuous innovation in esophageal cancer treatment.